An Assessment of the History of Christian Mission in Talensiland: Addressing the Issues of Conflict and Accommodation for Discipleship and Church Growth - Samuel Zuul Bayeti (Journal of Education and Learning Technology)
Christians throughout the ages have come to believe that the Great Commission, recorded in Matthew 28:19-20 enjoins them to proclaim the gospel to every person everywhere in the world. From biblical history as well as church history, it is evident that this mandate by Jesus to all Christians has been carried out resulting in the establishment of churches. The emergence of Christianity resulted in the formation of churches. Thus, Christians of all ages have sought to proclaim their faith as the vehicle for the salvation of non-Christians. The Christian faith, as a universal religion, encounters people in their various cultures wherever it is propagated. This paper therefore examined how the Christian faith was transmitted among the Talensi People of Ghana, and how it is being expressed by Talensi Christian converts as well as its impact on the Talensi society. Interviews and participant involvement formed the basis of data collection for the study. Key personalities who were contended that the success of any evangelistic activity among indigenous people highly depends upon how the Christian message is proclaimed, and understood by its intended audience. The paper concludes that for the Christian faith to take root in indigenous societies, it must take cognizance of the people’s culture. People do not need to abandon their cultural links in order to become Christians but rather can be assisted to express their faith relevantly in the light of their cultures. This paper adds to the scholarly discourse on the engagement between Christianity and African traditional culture as well as the history of religions and missions as academic disciplines.